LEGAL REGULATION OF SOLE PROPRIETORSHIP IN LITHUANIA: PAST, PRESENT, PERSPECTIVES - Mikelėnas, Valentinas (Teisė, 2016)
Article is prepared during the performance of the scientific research “The convergence and divergence of legal forms of business: does Lithuanian legal regulation is attractive in international context”, which is financed by the Research Council of Lithuania. The article deals with the evolution of legal regulation of individual business in Lithuania and with the present legal forms of business – individual entrepreneurship and individual enterprise. The legal regulation of individual entrepreneurship is analysed from the historical, statistical and comparative point of view. The conclusion is made that the number of individual enterprises and peoples, involved in individual entrepreneurship reflects entrepreneurship of all society. According to the official statistics the number of self-employed workers in Lithuania is about 13 percent of the total number of working-age population. The European Union average is 16.5 percent. According to this indicator, Lithuania is ahead of Finland (13.5 percent.), United Kingdom (14.5 percent.), Belgium (15.1 percent.), Slovakia (15.6 percent.), Netherlands (15.9 percent), Slovenia (16.9 percent.), Ireland (17.1 percent.), Czech Republic (17.9 percent.), Spain (17.9 percent.), Poland (21.8 percent.) Portugal (22.1 percent.), Italy (25.1 percent.), Greece (36.9 percent.). At present, there are four forms of individual business in Lithuania: 1) the individual enterprise having the status of legal person and functioning according to the Law on individual companies and the Civil Code; 2) agriculture farm (farmer), which does not have the status of legal person, acting on the basis of the Law on farmer‘s farm; 3) a natural person engaged in individual business activities on the basis of individual activity certificate; 4) a natural person engaged in individual business activities on the basis business certificate. The change of legal status of individual enterprise and their becoming a legal person can be considered to be one of the reasons behind the decline in their numbers in Lithuania. A legal person status granted to an individual enterprise is to be regarded negatively for several reasons. First, it has become more complex to start business, because of the need to prepare the articles of association, and take other actions necessary for the establishment of legal persons (Art. 4 of the Law on individual enterprises). It also increases the costs and length of the establishment of business. Secondly, it has become more complex the liquidation procedure of individual enterprise. Third, the taxpayer is not only the natural person – the owner of the individual enterprise, but also the individual enterprise, as legal person, which is subject of corporate taxes, such as profit tax, real estate tax, etc.